Loosening of the mesothelial barrier as an early therapeutic target to preserve peritoneal function in peritoneal dialysis - Duk-Hee Kang (The Korean Society of Nephrology, 2020)
Phenotype transition of peritoneal mesothelial cells (MCs) including the epithelial-to-mesenchymal transition (EMT) is regarded as an early mechanism of peritoneal dysfunction and fibrosis in peritoneal dialysis (PD), producing proinflammatory and pro-fibrotic milieu in the intra-peritoneal cavity. Loosening of intercellular tight adhesion between adjacent MCs as an initial process of EMT creates the environment where mesothelium and submesothelial tissue are more vulnerable to the composition of bio-incompatible dialysates, reactive oxygen species, and inflammatory cytokines. In addition, down-regulation of epithelial cell markers such as E-cadherin facilitates de novo acquisition of mesenchymal phenotypes in MCs and production of extracellular matrices. Major mechanisms underlying the EMT of MCs include induction of oxidative stress, pro-inflammatory cytokines, endoplasmic reticulum stress and activation of the local renin-angiotensin system. Another mechanism of peritoneal EMT is mitigation of intrinsic defense mechanisms such as the peritoneal antioxidant system and anti-fibrotic peptide production in the peritoneal cavity. In addition to use of less bio-incompatible dialysates and optimum treatment of peritonitis in PD, therapies to prevent or alleviate peritoneal EMT have demonstrated a favorable effect on peritoneal function and structure, suggesting that EMT can be an early interventional target to preserve peritoneal integrity.